Plasmacytoid Urothelial Carcinomas – A Chemo-sensitive Cancer with Poor Prognosis, and Peritoneal Carcinomatosis - Dayyani, Farshid (J Urol, 2012)
PURPOSE: Plasmacytoid urothelial carcinoma (PUC) is a rare variant histology with poorly defined clinical behavior. We report clinical outcomes information on patients with predominant PUC. MATERIALS AND METHODS: Retrospective analysis of treatments and outcomes in patients with predominant PUC seen at MD Anderson Cancer Center from 1990–2010. Kaplan-Meier method was used to calculate Overall (OS) and progression-free survival (PFS). RESULTS: 31 patients were identified (median age:63.5yrs; 83.3% male; TNM stage:cT1N0,n=4;cT2N0,n=7;cT3b-4aN0,n=5; cT4b, N+ or M+ n = 15). Median OS for all patients was 17.7months (Stage I-III vs IV: 45.8 vs 13.3mo). Of 16 patients with potentially surgically resectable PUC (<=pT4aN0M0) 5 received neo-adjuvant chemotherapy, 10 had initial surgery, and one was treated with TURBT alone. Despite pathologic downstaging in 80% of patients treated with neo-adjuvant chemotherapy, relapses were common and there was no difference in survival between patients treated with neo-adjuvant chemotherapy compared to initial surgery, even though adjuvant chemotherapy was given in 7 patients. Surgical upstaging with positive margins was also common with surgery alone. The most common site of recurrence was in the peritoneum (19/23), with relapses occurring even in those with pCR at surgery. In patients presenting with metastatic disease who were treated with chemotherapy, the median survival was 12.6 months. CONCLUSIONS: PUC is a very aggressive subset with overall poor outcomes. Although downstaging is seen with neoadjuvant chemotherapy, there are few long-term survivors. There is a strong predilection for recurrences along the peritoneal lining.